2D nano-Y2O3:Eu3+ photoluminescence with different preparation methods and annealing temperatures. (16th March 2017) - Zhou, Jun; Zhu, Yanhua; Liu, Huangqing; Chai, Yifeng; Yang, Yibo; Zhang, Qingjun; Wang, Lingling
Abstract: Y2 O3 :Eu 3+ (YOE) material is an important photoluminescence (PL) material. In this paper, YOE nano-powder was prepared by the low-temperature combustion method (LTC) and sol-gel method (SG), and annealed with different temperatures, respectively. The influence of the preparation methods and annealing temperature on the optical properties of YOE were well studied. The as-synthesized nano-YOE samples were characterized by x-ray diffraction (XRD), PL spectra, and Fourier transform infrared spectroscopy (FTIR). Results show that with the increase in annealing temperature, the charge transfer band (CTB) of samples blue-shifts and shows higher intensity. FTIR results indicate that low emission intensity decreases luminescence intensity and deteriorates the optical properties of nano-YOE. We also studied the spectral intensity changes before and after laser-induced, which shows the intensity of significant changes over time.